Pengembangan Alat Penyiraman Otomatis Smart Plant Berbasis Internet of Things - Sukirno; Suhendar, Heri; Nur’aini, Shifa (Institut Teknologi Garut, 2025)
Plants will grow better and produce benefits forother living things with regular watering. An Internet of Things (IoT)-based plant watering device is a modern solution that utilizes technology to automate and improve plant watering efficiency. The urgency of this research is to help optimize water usage and facilitate plant empowerment with integrated technology based on IoT. The purpose of this research is to develop an IoT-based smart plant automatic watering tool. The novelty is in the system design method and the object under study in the form of light efficiency and speed of the plant nutrition control system. Analysis in data processing with artificial intelligence. The use of WIMOS ESP8266 DI microcontroller and monitoring using Blynk integration. The method used in this research is the experimental method. Designing an IoT-based smart plant automatic watering device. The system design will produce information about soil moisture from the DHT22 sensor then displayed on the Blynk LCD. The integration of IoT, Blynk and data analysis using artificial intelligence provides a new contribution, with monitoring and management of dara in real time so that information is faster and more accurate.